The Effect of Sperm DNA Fragmentation on Invitro Fertilization: From Embryo Development to Clinical Pregnancy Success. - Mohan, Divya; Murugan, M Murugan (Journal of Neonatal Surgery, 2025)
The prevalence of infertility affects reproductive-aged couples worldwide, with male characteristics responsible for nearly half of the cases. Traditional semen analysis often fails to diagnose male infertility, as infertile men exhibit normal results. Sperm DNA (Deoxyribonucleic acid) fragmentation (SDF) has gained attention for its diagnostic value in predicting male fertility outcomes, especially in intracytoplasmic sperm injection (ICSI) procedures. The proposed study investigates the effect of SDF on fertilization rates, clinical pregnancy results, and embryo quality. A total of 202 couples were selected from Yana Women Hospital and Fertility Centre, and other hospitals in Kerala. The DNA fragmentation index (DFI) values of the test group (DFI 30) and the control group (DFI 30) were used to separate the participants into two groups. The number of retrieved oocytes and MII oocytes showed no significant difference. The number of high-quality embryos was found to be negatively correlated with sperm DFI. The results demonstrated that there was an inverse relationship between clinical pregnancy rate and DFI, which was statistically significant ( ). Additional findings presented that high DFI is significantly related to reduced sperm concentration, inferior morphology, and lower motility. Pearson correlation revealed an inverse relationship between high DFI and clinical pregnancy rate (r = -0.1316, p = 0.001), highlighting the effect of DNA integrity on reproductive success. Therefore, in assisted reproductive technologies (ART) cycles, high DFI levels signify lower fertility rates, clinical pregnancy rates, and embryo quality.